Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1136/bmjopen-2014-006431
|View full text |Cite
|
Sign up to set email alerts
|

Health system reforms, violence against doctors and job satisfaction in the medical profession: a cross-sectional survey in Zhejiang Province, Eastern China

Abstract: ObjectiveTo explore the factors influencing doctors’ job satisfaction and morale in China, in the context of the ongoing health system reforms and the deteriorating doctor–patient relationship.DesignCross-sectional survey using self-completion questionnaires.Study settingThe survey was conducted from March to May 2012 among doctors at the provincial, county and primary care levels in Zhejiang Province, China.ResultsThe questionnaire was completed by 202 doctors. Factors which contributed most to low job satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 29 publications
12
122
1
1
Order By: Relevance
“…According to the data of Wu D et al the most important factors of the negative influence of doctors' satisfaction are the low incomes and duration of working day. Only 30,0 % of Chinese doctors were satisfied with their salary and 50,0 % of doctors -with duration of their working day [8]. This idea is also shared by Atif K et al that also established the negative influence of salary on the satisfaction with work [21].…”
Section: Discussion Of Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…According to the data of Wu D et al the most important factors of the negative influence of doctors' satisfaction are the low incomes and duration of working day. Only 30,0 % of Chinese doctors were satisfied with their salary and 50,0 % of doctors -with duration of their working day [8]. This idea is also shared by Atif K et al that also established the negative influence of salary on the satisfaction with work [21].…”
Section: Discussion Of Resultssupporting
confidence: 50%
“…The aforesaid testifies to the doctors' dissatisfaction with their profession, to their disillusion. The analogous dissatisfaction was determined also among Chinese doctors [8]. According to the data of Wu D. et al, in China only 4,5 % want their children to become doctors [8].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with more developed regions, healthcare providers in less developed regions had lower incomes, experienced relaxed regulations, and were more likely to profit from overprescribing antibiotics [7,15,20]. Our findings also indicated that, even when doctors were initially unwilling to prescribe antibiotics, more students pressured doctors to prescribe antibiotics in less developed regions compared to developed regions [16,21]. …”
Section: Discussionmentioning
confidence: 79%
“…thresholds, unrealistic preoperative expectations, and psychological disorders [1,4]. Recent studies [10,13] reveal that orthopaedic surgeons in China have experienced psychological and even physical threats by patients or family members, suggesting perhaps that it is more challenging to establish a healthy doctor-patient relationship in Asia than in other countries.…”
Section: Patients Who Challenge Usmentioning
confidence: 99%